ANALYSIS OF THE RELATIONSHIP OF MOTHER'S KNOWLEDGE WITH THE INCIDENT OF DIARRHEA IN TODDLER IN THE BATOH HEALTH CENTER, KOTA BANDA ACEH - Zahara, Hafni; Putri, Rosalia; Destry, Ririn (Transpublika Publisher, 2023)
The study aimed to investigate the relationship between maternal knowledge and the occurrence of diarrhea in toddlers within the jurisdiction of the Batoh Community Health Center in Banda Aceh City. Diarrhea is identified as the leading cause of death in infants and toddlers, leading to poor nutritional status and growth failure. Accidental sampling was utilized as the method for selecting participants in this study. The findings revealed that out of the total participants, 8 individuals (33.3%) had low maternal knowledge regarding the incidence of diarrhea in toddlers, while 14 individuals (27.5%) had high knowledge in this area. On the other hand, 16 individuals (66.7%) had low knowledge regarding the absence of diarrhea in toddlers, while 37 individuals (72.5%) had high knowledge in this area. To determine the relationship between maternal knowledge and the occurrence of diarrhea in toddlers, the Chi-Square test was conducted. The test yielded a p-value of 0.803, which indicates that there is no significant relationship between maternal knowledge and the occurrence of diarrhea in toddlers within the Batoh Community Health Center's jurisdiction in Banda Aceh City. These findings suggest that maternal knowledge alone may not be the sole determinant of the occurrence of diarrhea in toddlers. Other factors such as hygiene practices, access to clean water, and proper sanitation may also play a significant role in preventing diarrhea in this population. Further research is needed to explore these factors and develop comprehensive interventions to reduce the incidence of diarrhea in infants and toddlers in this community.